A reticulated copper-iron sulfide nanosheet electrode material, a preparation method therefor, and an application thereof

CN115376835BActive Publication Date: 2026-09-08QINGDAO UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211142248.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-20
Publication Date
2026-09-08
Estimated Expiration
2042-09-20

AI Technical Summary

Technical Problem

但这些电极材料大部分为厚的纳米片结构,尤其是铜铁硫化物作为超级电容器电极材料,制备时需要特殊装置、高温高压、长的反应时间等条件,作为正极材料的比电容值为50~219F g-1(远低于广泛研究且电容值高达1000-3200F g-1的镍钴基化合物),这大大限制了其在工业生产中的推广和应用

Benefits of technology

[0018] (1) This invention uses copper chloride and iron chloride in different proportions as copper and iron sources, urea as precipitant, NH4F as structure directing agent, and a mixed solution of deionized water and ethylene glycol in a volume ratio of 2:1 as solvent to synthesize large nanosheets of interleaved and interconnected copper-iron sulfide precursors by solvothermal method. These nanosheets grow firmly on a foamed nickel conductive substrate, which helps to improve the structural stability of the electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115376835B_ABST
    Figure CN115376835B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of reticular copper iron sulfide nanosheet electrode materials and its preparation method and application, including the following steps: foam nickel is placed in the mixed solution of copper chloride, iron chloride, urea and ammonium fluoride prepared with deionized water and ethylene glycol, copper iron sulfide precursor nanometer thick sheet is prepared by solvent thermal reaction with staggered distribution;Then it is heated in the anhydrous ethanol solution of thioacetamide in ground glass bottle with cover using liquid phase method, gap is generated by moving ground glass bottle cover upwards, anhydrous ethanol gradually volatilizes, solution concentration constantly improves, ion exchange and etching process are carried out, material produces sulfidation and significant structure reconstruction, and foam nickel load reticular copper iron sulfide nanosheet array is obtained.It has high specific surface area and a large number of active sites, which is very beneficial to its electrochemical performance.The electrode material has very high area / mass ratio capacitance and good rate performance, and can be directly used as the next generation of high-performance supercapacitor electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of novel energy storage materials and nanomaterial synthesis technology, specifically relating to a network copper-iron sulfide nanosheet electrode material, its preparation method, and its application in supercapacitor electrode materials. Background Technology

[0002] With the continuous growth of the global population and the increasing prosperity of the economy, per capita energy consumption has increased significantly, and global energy consumption is expected to increase by one-third by 2040. Traditional fossil fuels emit large amounts of carbon dioxide, nitrous oxide, and other gases during combustion, contributing to the greenhouse effect and causing global warming, melting polar ice caps, rising sea levels, abrupt climate change, and severe smog. To address global warming, countries are controlling carbon emissions and vigorously developing green and renewable energy sources such as solar and wind power. However, the intermittency of these sources, leading to grid fluctuations, is a significant problem. Simultaneously, the rapid development of green and environmentally friendly electric vehicles and energy storage rail vehicles presents both tremendous historical opportunities and challenges for new energy storage and conversion devices, and is constantly fostering new technological breakthroughs.

[0003] As a novel energy storage device, supercapacitors offer advantages over batteries, including high power density, fast charging speed, long lifespan, wide operating temperature range, and safety and environmental friendliness. They hold broad application prospects in electric / hybrid vehicles, energy storage rail vehicles, rail transit braking energy recovery systems, heavy machinery, wind turbine pitch control, and internal combustion locomotive starting systems. However, most commercially available supercapacitors currently composed of activated carbon have a limited energy density (3-6 Wh / kg). -1 The cost is far lower than that of lithium batteries (100-200Wh / kg). -1 However, these methods cannot meet the demands for increasingly high-energy-density devices. Based on different energy storage mechanisms, supercapacitors are divided into electric double-layer capacitors, where the charging / discharging process involves only physical adsorption processes of charge rearrangement, and pseudocapacitors, where a Faraday electrochemical reaction occurs. The latter has a much higher energy density than the former, thus pseudocapacitors have become a current research hotspot. According to the energy density formula E = 1 / 2CV... 2 Improving the specific capacitance C of electrode materials is the main way to increase the energy density of supercapacitors. Currently, the electrode materials for pseudocapacitors under research mainly include transition metal hydroxides, oxides, sulfides, and phosphides, including the earliest discovered noble metal oxide RuO2, the more expensive nickel-based and cobalt-based metal compounds such as Ni(OH)2, NiO, Co3O4, NiCo2O4, ZnCo2O4, CuCo2O4, NiCo2S4, and NiCoP, as well as copper and iron oxides CuO and Fe2O3, which are abundant and inexpensive on Earth. However, research on copper-iron bimetallic compounds as electrode materials is very limited.

[0004] Copper-iron bimetallic compounds mainly include hydroxides, oxides and sulfides. As a type of multifunctional nanomaterial with wide availability and low price, they can be widely used in catalysts, photothermal agents for targeted photothermal therapy of cancer / tumors, lithium batteries and supercapacitors. (1) There have been reports on their application as catalysts in water splitting for hydrogen production and degradation of toxic organic compounds. For example, Mallikarjun Bhavanari et al. synthesized CuFe LDH nanosheet cathode electrocatalysts for water splitting for hydrogen production (Mallikarjun Bhavanari, et al. CuFe electrocatalyst for hydrogen evolution reaction in alkaline electrolysis. International Journal of Hydrogen Energy, 2021, 46: 35886-35895 and Mallikarjun Bhavanari, et al. New insights into interface charge-transfer mechanism of copper-iron layered double hydroxide cathodic electrocatalyst in alkaline electrolysis. Journal of Environmental Chemical Engineering, 2022, 10: 10728). Chinese invention patent CN113289682B, "A CuFe2S3-polydiaminopyridine three-dimensional composite catalyst and its preparation method and application", discloses a catalyst that can be used for the remediation of water bodies polluted by toxic organic compounds phenanthrene. It can rapidly degrade phenanthrene in water by activating sodium persulfate to generate free radicals, and has high catalytic efficiency.(2) In the field of targeted photothermal therapy for cancer / tumor, Wang et al. used Fe(NO3)3·9H2O and Cu(NO3)2·6H2O as metal salts, NaOH as the alkali source, and added NaNO3 and formamide. The mixture was stirred at room temperature for 1 hour under N2 protection to obtain a colloidal solution. After centrifugation and dialysis, CuFe-LDH was obtained. After sulfidation, ultrathin CuFe2S3 nanosheet powder material was obtained. The nanosheet diameter was about 63 nm and the thickness was about 1.5 nm. It can be used as a highly efficient nanophotothermal agent for targeted photothermal therapy for cancer / tumor (Sa Wang, et al. Ultrathin CuFe2S3 nanosheets derived from CuFe-layered double hydroxide as an efficient nanoagent for synergistic chemodynamic and NIR-II photothermal therapy. Chemical Engineering Journal, 2021, 419: 129458). (3) In terms of lithium battery materials, for example, Hua Li et al. synthesized CuFe2O4 material by hydrothermal method and used it as a lithium battery anode material. The morphology is approximately micron-sized flakes with a particle size of about 0.6-1.2 μm. The specific capacity of the first charge and discharge cycle was 484.2 mAh·g. -1 and 512.5mAh·g -1 The 70th time was 228.7 mAh·g -1 and 233.3 mAh·g -1 (Hua Li, et al. Study on the synthesis and performance of CuFe2O4 lithium battery anode material by hydrothermal method. Journal of Hubei Second Normal University, 2015, (8) 32: 1-4). (4) In the field of supercapacitors, researchers have conducted some preliminary studies and explorations on copper iron oxides and sulfides. For example, Vikas Sharma et al. prepared a precursor by solvothermal reaction for 24 h, and then calcined it at 500℃ to obtain CuFe2O4 hierarchical porous superstructure electrode material, which can be used as a catalyst for supercapacitors and water cracking to produce hydrogen. As a supercapacitor electrode, the current density is 1A g in a 2M KOH solution. -1 The capacity is 160mAh g -1 (approximately 830g) -1(Vikas Sharma, et al. Pragmatically designed tetragonal copper ferrite super-architectures as advanced multifunctional electrodes for solid-state supercapacitors and overall watersplitting. Chemical Engineering Journal, 2021, 415:127779). Shubhangi B. Bandgar et al. from India prepared planoporous CuFe2O4 nanosheet electrode materials using a rotary reflux chemical method (110℃, 18h) combined with calcination at 500℃ on a stainless steel mesh, achieving a record-breaking capacity of 1164 C g. -1 / 1940F g -1 (Shubhangi B. Bandgar, et al. Rotational reflux chemistry approach derived flat holey CuFe2O4 nanosheets for supercapacitors application. Materials Letters, 2020, 279:128514). P. Rupa Ranjani et al. from India synthesized large CuFeS2 nanosheet powder materials with an average length of 0.84 μm using a one-step solvothermal method (180 °C, 11 h). Electrodes were prepared using conductive materials and binders at 1 A g. -1 The highest specific capacitance is 219F g. -1 (P. Rupa Ranjani, et al. Solvothermal synthesis of CuFeS2 nanoflakes as a promising electrode material for supercapacitors. Journal of Energy Storage, 2021, 33: 102063). Hope E. Nsude et al. synthesized CuFeS2 nanoparticles mediated by Mimosa leaf extract for photocatalytic degradation of methylene blue and supercapacitor applications, achieving a yield of 1.0 A g. -1 The specific capacitance at that time is 50F g -1(Hope E. Nsude, et al. Green synthesis of CuFeS2 nanoparticles using mimosa leaves extract for photocatalysis and supercapacitor applications. J Nanopart Res, 2020, 22:352). Akbar Mohammadi Zardkhoshoui et al. from Iran obtained CuFeS2 nanosheets approximately 2 μm long by solvothermal sulfidation for 12 h. These nanosheets were used as anode materials for supercapacitors in a potential window of -1.2 V to 0 V and a current density of 1 A g. -1 The specific capacitance at that time was 654.3 F g. -1 (218.1mA hg -1 ). (Akbar MohammadiZardkhoshoui, et al. Ultra-high energy density supercapacitors based on metal–organic framework derived yolk–shell Cu–Co–P hollow nanospheres and CuFeS2nanosheet arrays. Dalton Trans., 2020, 49, 3353–3364).

[0005] Although copper-iron hydroxides, oxides, and sulfides have been widely used as multifunctional nanomaterials in various fields, their application in supercapacitor electrode materials has gradually expanded in recent years. However, most of these electrode materials have thick nanosheet structures. In particular, copper-iron sulfides, when used as supercapacitor electrode materials, require special equipment, high temperature and pressure, and long reaction times for preparation. As positive electrode materials, their specific capacitance ranges from 50 to 219 F g. -1 (far lower than widely studied values ​​and capacitance values ​​as high as 1000-3200F g) -1 The limited availability of nickel-cobalt based compounds significantly restricts their promotion and application in industrial production. Transition metal sulfides, due to the lower electronegativity of sulfur compared to oxygen in metal oxides, exhibit superior electrochemical activity and higher conductivity, along with advantages such as smaller volume expansion and higher mechanical stability, thus possessing higher capacitance and wider electrochemical applications. Currently, the highest specific capacitance of copper-iron sulfides (219 F g) is... -1 It is also far lower than the copper-iron oxide (1940F g) reported in the literature. -1Therefore, developing a green, energy-saving, and environmentally friendly synthesis process that is simple to prepare, low in cost, reduces high-temperature and high-pressure conditions, shortens reaction time, and improves material utilization, in order to obtain copper-iron sulfide nanoelectrode materials that avoid the use of binders, have unique and novel morphologies, numerous electroactive sites, and possess high area-to-mass specific capacitance and good rate performance, has significant theoretical research and industrial large-scale production application value. Summary of the Invention

[0006] To address the shortcomings of existing copper-iron sulfide electrode materials, such as the need for high temperature and high pressure, long reaction time, and low capacity of the resulting nanomaterials, this invention aims to provide a mesh-like copper-iron sulfide nanosheet electrode material, its preparation method, and its applications. The prepared electrode material possesses a large number of active sites, excellent area / mass specific capacitance, and good rate performance, and can be directly used as the electrode for next-generation high-performance supercapacitors without binders.

[0007] To achieve the objective of this invention, the technical solution of this invention is a mesh-like copper-iron sulfide nanosheet electrode material and its preparation method, comprising the following preparation steps:

[0008] (1) CuCl2·2H2O, FeCl3·6H2O, NH4F and urea were dissolved in a mixed solution of deionized water and ethylene glycol, and the solution was magnetically stirred to obtain a homogeneous precursor solution.

[0009] (2) The precursor solution was transferred into the polytetrafluoroethylene liner of the reactor, and the pretreated nickel foam was added and sealed. The reaction was carried out in a dry oven with a forced airflow. After the reaction, the solution was cooled to room temperature, the nickel foam was removed, washed in deionized water and anhydrous ethanol, and dried in a dry oven with a forced airflow to obtain nickel foam-supported nano-copper iron sulfide precursor.

[0010] (3) Thioacetamide was dissolved in anhydrous ethanol and magnetically stirred for 20 min to obtain a homogeneous solution. The solution was then transferred to a 100 mL frosted glass bottle and nickel foam-supported nano-copper-iron sulfide precursor was added. The bottle was sealed with a glass cap and placed in a drying oven for liquid-phase reaction. The anhydrous ethanol solution gradually evaporated, and the sulfur source concentration increased continuously, accelerating the sulfidation reaction. After the reaction was completed, the sample was cooled to room temperature, removed, and washed several times with deionized water and anhydrous ethanol. The sample was then dried in a forced-air drying oven to obtain nickel foam-supported nano-copper-iron sulfide.

[0011] In step 1, the total concentrations of CuCl2·2H2O and FeCl3·6H2O in the mixed solution were 50–75 mM, NH4F was 140 mM, and urea was 240 mM.

[0012] In step 1, the volume ratio of deionized water to ethylene glycol in the mixed solution is 2:1.

[0013] Step 2 involves pretreating the nickel foam by ultrasonically acid washing it in a 3M HCl solution for 10-15 minutes to remove surface oxides and impurities. Then, it is ultrasonically cleaned in deionized water 3-5 times until the solution is neutral. After soaking in anhydrous ethanol, it is dried at 60°C for 50 minutes to obtain pretreated nickel foam.

[0014] The temperature of the solvothermal reaction in step 2 is 100–140℃, and the reaction time is 8–12 h.

[0015] In step 3, the concentration of thioacetamide in the homogeneous solution is 30–50 mM.

[0016] In step 3, the liquid phase reaction temperature is 80–150℃, and the reaction time is 2–6 hours.

[0017] Compared with the prior art, the present invention has the following advantages:

[0018] (1) This invention uses copper chloride and iron chloride in different proportions as copper and iron sources, urea as precipitant, NH4F as structure directing agent, and a mixed solution of deionized water and ethylene glycol in a volume ratio of 2:1 as solvent to synthesize large nanosheets of interleaved and interconnected copper-iron sulfide precursors by solvothermal method. These nanosheets grow firmly on a foamed nickel conductive substrate, which helps to improve the structural stability of the electrode.

[0019] (2) This invention employs a liquid-phase method using a capped frosted glass bottle to vulcanize the precursor in an anhydrous ethanol solution of thioacetamide, resulting in a binder-free nickel-supported network of copper-iron sulfide nanosheet electrode material. During heating, the pressure inside the glass bottle gradually increases, the frosted bottle cap moves upward to create a gap, and the anhydrous ethanol gradually evaporates, maintaining a pressure inside the glass bottle that is higher than atmospheric pressure. As the volume of the solution inside the bottle decreases, the concentration of thioacetamide continuously increases, which can significantly improve the vulcanization rate and sulfur source utilization, and shorten the vulcanization time. During the vulcanization process, the copper-iron sulfide precursor nanosheets undergo ion exchange and etching, and the material gradually vulcanizes and undergoes significant structural reconstruction, forming sheet-like and spherical coral-like structures. These structures are composed of unique and novel interconnected network of copper-iron sulfide nanosheets, which can significantly increase the specific surface area and active sites of the nanomaterial, greatly enhancing its electrochemical performance.

[0020] (3) The foamed nickel-supported mesh copper-iron sulfide nanosheet array electrode of the present invention has excellent capacitance performance at a current density of 5 mA cm⁻¹. -2 The area and mass specific capacitances at that time were as high as 10.06 and 3353.8 F g, respectively. -1 At a high current density of 50 mA cm⁻¹ -2The capacitance retention rate was 67.9%. This nanomaterial can be directly applied to next-generation high-performance supercapacitors and also has broad application prospects in lithium-ion batteries and electrocatalysis. The overall nanomaterial preparation process is simple and convenient, requires no complex equipment or devices, has mild reaction conditions, high sulfur source utilization, is green and environmentally friendly, and is suitable for large-scale industrial production. Attached Figure Description

[0021] Figure 1 Scanning electron microscope (SEM) image of the nickel foam-supported copper-iron sulfide precursor prepared in Example 1.

[0022] Figure 2 This is a scanning electron microscope (SEM) image of the nickel foam loaded with copper-iron sulfides prepared in Example 1.

[0023] Figure 3 Electrochemical performance test results of the nickel foam supported copper-iron sulfide prepared in Example 1: (a) Cyclic voltammetry curves at different scan rates; (b) Charge-discharge curves at different current densities; (c) Area / mass specific capacitance curves at different current densities.

[0024] Figure 4 The nickel-supported copper-iron sulfide foams prepared in Examples 2 to 6 were subjected to a current density of 10 mA cm⁻¹. -2 Charge-discharge curves.

[0025] Figure 5 The nickel-supported copper-iron sulfides prepared for Comparative Examples 1 and 2 were subjected to a current density of 10 mA cm⁻¹. -2 Charge-discharge curves. Detailed Implementation

[0026] To make the technical problem to be solved, the technical solution, and the beneficial effects of the present invention clearer, the present invention will be further described in detail below with reference to embodiments, comparative examples, and accompanying drawings. It should be understood that the embodiments described are only for explaining the present invention and are not intended to limit the scope of the present invention.

[0027] Example 1

[0028] (1) Weigh 0.2066g ​​(20mM) of CuCl2·2H2O, 0.6553g (40mM) of FeCl3·6H2O, 0.3241g (140mM) of NH4F and 0.8735g (240mM) of urea respectively, dissolve them in a mixed solution of 40mL of deionized water and 20mL of ethylene glycol, and stir magnetically for 20min to obtain a homogeneous solution; ultrasonically clean 2.2cm×5cm nickel foam in 3M HCl solution for 15min to remove oxides and impurities on the surface, then ultrasonically clean it 3-5 times in deionized water until the solution is neutral, soak it in anhydrous ethanol, and then dry it in a forced-air drying oven at 60℃ for 50min to obtain pretreated nickel foam;

[0029] (2) The above uniform solution was transferred into the polytetrafluoroethylene liner of the reactor, and the pretreated nickel foam was added and sealed. The reaction was carried out in a drying oven at 120°C for 10 hours. After the reaction, the solution was cooled to room temperature, the nickel foam was removed, washed several times in deionized water and anhydrous ethanol, and dried at 60°C for 10 hours to obtain nickel foam-supported nano-copper iron sulfide precursor.

[0030] (3) Weigh 0.121 g (40 mM) of thioacetamide, dissolve it in 40 mL of anhydrous ethanol, and stir magnetically for 20 min to obtain a homogeneous solution; then transfer the solution to a 100 mL ground glass bottle and add the copper-iron sulfide precursor, cover with a glass cap, and place in a drying oven for liquid-phase reaction at 110 °C for 4 h. The anhydrous ethanol solution gradually evaporates and is then dried; after the reaction is complete, cool to room temperature, remove the sample, wash it three times with deionized water and once with anhydrous ethanol, and dry it at 60 °C for 10 h to obtain nickel foam-supported nano-copper-iron sulfide with an active material loading of 3.0 mg cm⁻¹. -2 .

[0031] Scanning electron microscope images of the prepared nickel-supported network nano-copper-iron sulfide precursor are shown below. Figure 1 As can be seen from the low-magnification image (a), the precursor nanosheets are uniformly covered on the nickel foam substrate, with some blocky micron particles present in some areas. From the magnified images (b) and (c), it can be seen that the nanosheets are interconnected and cross-distributed, with a large number of pores between them. In the further magnified image (d), it can be seen that the nanosheets are about 110 nm thick and have an average length of about 3 μm. They are relatively large nanosheets with very smooth surfaces, which is detrimental to their electrochemical performance.

[0032] Scanning electron microscope images of the prepared nickel-supported network of copper-iron sulfides are shown below. Figure 2As can be seen from the lower magnification image (a), the sulfides on the surface of the nickel foam consist of a coral-like morphology composed of numerous plates and spheres, which should have been formed by the precursor nanosheets and micron particles during the sulfidation etching process. The magnified images (b) and (c) show that these coral-like structures are composed of numerous interconnected nanosheets. The high magnification image (d) clearly shows that these numerous interconnected nanosheets form a network structure, with an average nanosheet thickness of 6.5 nm and numerous pores between the nanosheets, with a size of approximately 100 nm. As can be seen, during the heating process, the pressure inside the glass bottle gradually increases, the frosted bottle cap moves upward to create a gap, and the anhydrous ethanol gradually evaporates, maintaining the pressure inside the glass bottle above atmospheric pressure and essentially constant. As the volume of the solution inside the bottle decreases, the concentration of thioacetamide continuously increases, which can significantly improve the sulfidation rate and sulfur source utilization, and shorten the sulfidation time of the electrode material. During the sulfidation process, the copper-iron sulfide precursor nanosheets undergo ion exchange and etching, and the material gradually sulfidates and undergoes significant structural reconstruction, forming plate-shaped and spherical coral-like morphologies. These are composed of unique and novel interconnected network copper-iron sulfide nanosheets, which have a larger specific surface area and more active sites, which is very beneficial to their electrochemical performance.

[0033] A three-electrode system was constructed using the prepared nickel-foamed, supported, network-like copper-iron sulfide nanosheet electrode material as the working electrode, a platinum wire as the counter electrode, and an Ag / AgCl electrode as the reference electrode. (6 mol L) -1 Using KOH aqueous solution as the electrolyte, electrochemical performance tests were conducted, including cyclic voltammetry and constant current charge-discharge tests. The constant current test current density was 5–50 mA cm⁻¹. -2 .

[0034] The electrochemical performance test results of the prepared nickel foam supported network copper-iron sulfide nanosheet electrode material are shown in the figure. Figure 3 . Figure 3 (a) shows the cyclic voltammetry curves at different scan rates. Each curve has a distinct redox peak, indicating that a pseudocapacitive reaction occurs. Figure 3 (b) shows the constant current charge-discharge curves under different current densities. All curves have obvious potential plateaus, further proving that the electrodes undergo pseudocapacitive redox reactions. Figure 3 (c) shows the area / mass capacitance curves at different current densities of 5, 10, 20, 30, and 50 mA cm⁻¹. -2 The areal capacitances were 10.06, 8.94, 7.29, 6.74, and 6.45 F / cm, respectively. -2 The specific capacitances were 3353.8, 2978.8, 2429.4, 2247.2, and 2149.1 F g, respectively. -1 At a high current density of 50 mA cm-2 The capacitance retention rate was 67.9%. This demonstrates that the prepared nickel-foamed, supported, network-like copper-iron sulfide nanosheet electrode material possesses both high areal and mass specific capacitance, as well as excellent rate performance, showing great potential as a next-generation high-performance supercapacitor electrode material.

[0035] Example 2

[0036] Example 2 differs from Example 1 in that the copper-iron sulfide precursor in step (3) is reacted in the liquid phase at 80°C for 4 hours. Other preparation conditions and processes are the same as in Example 1. A nickel-foamed, nano-copper-iron sulfide (80°C) electrode material was obtained, with an active material loading of 1.3 mg / cm³. -2 .Depend on Figure 4 As shown in curve (a), the electrode operates at 10 mA cm⁻¹ -2 The area and mass specific capacitances are 3.59 F / cm². -2 and 2764.6F g -1 .

[0037] Example 3

[0038] Example 3 differs from Example 1 in that the copper-iron sulfide precursor in step (3) is reacted in the liquid phase at 100°C for 4 hours. Other preparation conditions and processes are the same as in Example 1. A nickel foam-supported nano-copper-iron sulfide (100°C) electrode material was obtained, with an active material loading of 1.5 mg / cm³. -2 .Depend on Figure 4 As can be seen from curve (b), the electrode operates at 10 mA cm⁻¹ -2 The area and mass specific capacitances are 4.03 F / cm². -2 and 2684.6F g -1 .

[0039] Example 4

[0040] Example 4 differs from Example 1 in that the copper-iron sulfide precursor in step (3) is reacted in the liquid phase at 120°C for 4 hours. Other preparation conditions and processes are the same as in Example 1. A nickel foam-supported nano-copper-iron sulfide (120°C) electrode material was obtained, with an active material loading of 3.2 mg / cm³. -2 .Depend on Figure 4 As can be seen from curve (c), this electrode operates at 10 mA cm⁻¹ -2 The area and mass specific capacitances are 6.63 F / cm². -2 and 2071.0F g -1 .

[0041] Example 5

[0042] Example 5 differs from Example 1 in that the copper-iron sulfide precursor in step (3) is reacted in the liquid phase at 130°C for 4 hours. Other preparation conditions and processes are the same as in Example 1. A nickel foam-supported nano-copper-iron sulfide (130°C) electrode material was obtained, with an active material loading of 3.6 mg / cm³. -2 .Depend on Figure 4 As can be seen from curve (d), this electrode operates at 10 mA cm⁻¹ -2 The area and mass specific capacitances are 9.41 F / cm². -2 and 2614.9F g -1 .

[0043] Example 6

[0044] Example 6 differs from Example 1 in that the copper-iron sulfide precursor in step (3) is reacted in the liquid phase at 150°C for 4 hours. Other preparation conditions and processes are the same as in Example 1. A nickel foam-supported nano-copper-iron sulfide (150°C) electrode material was obtained, with an active material loading of 4.5 mg / cm³. -2 .Depend on Figure 4 As can be seen from curve (e), this electrode operates at 10 mA cm⁻¹ -2 The area and mass specific capacitances are 6.60 F / cm². -2 and 1466.7F g -1 .

[0045] Example 7

[0046] Example 7 differs from Example 1 in that the metal salt in step (2) is 0.775 g (75 mM) of CuCl2·2H2O. Other preparation conditions and processes are the same as in Example 1. A nickel foam-supported nano-copper iron sulfide (Cu:Fe = 1:0) electrode material was obtained, with an active material loading of 3.1 mg / cm³. -2 The electrode is at 10 mA cm⁻¹ -2 The area and mass specific capacitances are 2.19 F / cm². -2 and 705.6F g -1 .

[0047] Example 8

[0048] Example 8 differs from Example 1 in that the metal salts used in step (2) are 0.344 g (33.3 mM) of CuCl2·2H2O and 0.273 g (16.7 mM) of FeCl3·6H2O. Other preparation conditions and processes are the same as in Example 1. A nickel foam-supported nano-copper-iron sulfide (Cu:Fe = 2:1) electrode material was obtained, with an active material loading of 2.5 mg / cm³. -2 The electrode is at 10 mA cm⁻¹ -2The area and mass specific capacitances are 4.08 F / cm². -2 and 1633.9F g -1 .

[0049] Example 9

[0050] Example 9 differs from Example 1 in that the metal salts in step (2) are 0.387 g (37.5 mM) of CuCl2·2H2O and 0.614 g (37.5 mM) of FeCl3·6H2O. Other preparation conditions and processes are the same as in Example 1. A nickel foam-supported nano-copper-iron sulfide (Cu:Fe = 1:1) electrode material was obtained, with an active material loading of 2.6 mg / cm³. -2 The electrode is at 10 mA cm⁻¹ -2 The area and mass specific capacitances are 2.91 F / cm². -2 and 1117.7F g -1 .

[0051] Example 10

[0052] Example 10 differs from Example 1 in that the metal salt in step (2) is 0.819 g (50 mM) of FeCl3·6H2O. Other preparation conditions and processes are the same as in Example 1. A nickel foam-supported nano-copper iron sulfide (Cu:Fe = 0:1) electrode material was obtained, with an active material loading of 2.1 mg / cm³. -2 The electrode is at 10 mA cm⁻¹ -2 The area and mass specific capacitances are 4.09 F / cm². -2 and 1946.2F g -1 .

[0053] Comparative Example 1

[0054] The difference between Comparative Example 1 and Example 1 is that in step (1), 60 mL of deionized water was dissolved and the solution was magnetically stirred for 20 min to obtain a homogeneous solution. Other preparation conditions and processes were the same as in Example 1. A nickel-foamed electrode material loaded with copper-iron sulfide nanoparticles (pure water) was obtained, with an active material loading of 3.6 mg / cm³. -2 .Depend on Figure 4 As shown in curve (a), the electrode operates at 10 mA cm⁻¹ -2 The area and mass specific capacitances are 2.46 F / cm². -2 and 681.9F g -1 .

[0055] Comparative Example 2

[0056] The difference between Comparative Example 2 and Example 1 is that in step (3), the thioacetamide was 0.121 g (40 mM), and the Cu-Fe precursor was reacted in the liquid phase at 110 °C for 1 h. Other preparation conditions and processes were the same as in Example 1. A nickel foam-supported nano-copper-iron sulfide electrode material (110 °C, 1 h) was obtained, with an active material loading of 1.6 mg / cm³. -2 .Depend on Figure 4 As can be seen from curve (b), the electrode operates at 10 mA cm⁻¹ -2 The area and mass specific capacitances are 1.03 F / cm². -2 and 643.1F g -1 .

[0057] The nickel foam-supported copper-iron sulfide nanoparticle electrode material prepared in Example 1 operates at a current density of 5 mA cm⁻¹. -2 The area and mass specific capacitance at that time reached as high as 10.06 F cm⁻¹. -2 and 3353.8F g -1 At 50mA cm -2 The capacitance retention rate was 67.9% at a current density of 10 mA cm⁻¹. -2 The area and specific capacitance of the nanoelectrodes prepared in Examples 2 to 10 are much higher than those in Comparative Examples 1 and 2. The nanoelectrodes prepared in Examples 2 to 10 also have good electrochemical performance. They have great potential as electrode materials for the next generation of high-performance supercapacitors and have broad application prospects in the fields of lithium-ion batteries, electrocatalysis and targeted photothermal therapy for cancer / tumors.

[0058] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. For those skilled in the art, other variations or modifications can be made based on the above description and ideas. It is neither necessary nor possible to exhaustively describe all implementation methods here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a mesh-like copper-iron sulfide nanosheet electrode material, characterized in that, The preparation includes the following steps: (1) Dissolve CuCl2·2H2O, FeCl3·6H2O, NH4F and urea in a mixed solution of deionized water and ethylene glycol, and stir magnetically to obtain a homogeneous solution. (2) The above homogeneous solution was transferred into the polytetrafluoroethylene liner of the reactor, and the pretreated nickel foam was added and sealed. The reaction was carried out in a dry oven with a forced airflow. After the reaction, the solution was cooled to room temperature, the nickel foam was removed, washed in deionized water and anhydrous ethanol, and dried in a dry oven with a forced airflow to obtain nickel foam-supported nano-copper iron sulfide precursor. (3) Dissolve thioacetamide in anhydrous ethanol and stir magnetically to obtain a homogeneous solution. The solution was then transferred to a 100 mL frosted glass bottle, and nickel foam-supported nano-copper-iron sulfide precursor was added. The bottle was then sealed with a glass cap. The bottle was placed in a drying oven and heated to carry out a liquid-phase reaction. The anhydrous ethanol solution gradually evaporated, and the sulfur source concentration continuously increased, accelerating the sulfidation reaction. After the reaction was completed, the sample was cooled to room temperature, removed, and washed several times with deionized water and anhydrous ethanol. The sample was then dried in a forced-air drying oven to obtain nickel foam-supported nano-copper-iron sulfide.

2. The preparation method according to claim 1, characterized in that, In step (1), the total concentration of CuCl2·2H2O and FeCl3·6H2O in the mixed solution was 50~75mM, NH4F was 140mM and urea was 240mM; the molar ratio of the total metal salt, NH4F and urea was 10~15:28:

48.

3. The preparation method according to claim 1, characterized in that, In step (1), the volume ratio of deionized water to ethylene glycol in the mixed solution is 2:

1.

4. The preparation method according to claim 1, characterized in that, Step (2) The pretreatment process of nickel foam is to ultrasonically acid wash the nickel foam in 3M HCl solution for 10-15 minutes, then ultrasonically clean it in deionized water 3-5 times until the solution is neutral, soak it in anhydrous ethanol, and then dry it at 60℃ for 50 minutes to obtain pretreated nickel foam.

5. The preparation method according to claim 1, characterized in that, In step (2), the temperature of the solvothermal reaction is 100~140℃ and the reaction time is 8~12h.

6. The preparation method according to claim 1, characterized in that, In step (3), the concentration of thioacetamide is 30~50mM.

7. The preparation method according to claim 1, characterized in that, In step (3), the liquid phase reaction temperature is 80~150℃ and the reaction time is 2~6h.

8. The mesh-like copper-iron sulfide nanosheet electrode material synthesized by the preparation method according to any one of claims 1-7, characterized in that, By using liquid-phase sulfidation and structural reconstruction, the large copper-iron sulfide precursor nanosheets loaded with nickel foam are transformed into sheet-like and spherical coral-like structures, which are composed of a large number of interconnected network copper-iron sulfide nanosheets.

9. The application of a mesh-like copper-iron sulfide nanosheet electrode material prepared by the method according to any one of claims 1-7, characterized in that, The aforementioned mesh copper-iron sulfide nanosheet electrode material can be directly applied to next-generation high-performance supercapacitors, and also has broad application prospects in the fields of lithium-ion batteries and electrocatalysis.

Citation Information

Patent Citations

  • A CuFe2S3-polydiaminopyridine three-dimensional composite catalyst, its preparation method and application

    CN113289682B

  • Preparation method of self-supporting nanometer flake CoFeB supercapacitor electrode materials

    CN109119257A

  • KR20200139389A